2021
DOI: 10.3390/ijerph18094614
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Contacts Regarding Circulatory Conditions among Swedish Patients in Opioid Substitution Treatment, with and without On-Site Primary Healthcare

Abstract: Patients in Opioid Substitution Treatment (OST) have increased mortality and morbidity, with circulatory conditions suggested to be a contributing factor. Since OST patients tend to have unmet physical healthcare needs, a small-scale intervention providing on-site primary healthcare (PHC) in OST clinics was implemented in Malmö, Sweden in 2016. In this study, we assessed registered circulatory conditions and healthcare utilization in OST patients with and without use of on-site PHC. Patients from four OST clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These conditions were selected in compliance with side effects from OST medications, and in order to correspond to specific diagnoses assessed in previous research. Data on documented cardiovascular diseases has been previously reported [ 23 ] and was thus not included here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These conditions were selected in compliance with side effects from OST medications, and in order to correspond to specific diagnoses assessed in previous research. Data on documented cardiovascular diseases has been previously reported [ 23 ] and was thus not included here.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the findings indicating poor physical health and great healthcare needs among OST patients, a few previous studies have shown that patients in OST commonly have self-reported unmet healthcare needs and reluctance towards healthcare seeking [ 19 , 22 ]. A recent study from Malmö, Sweden, showed low rates of circulatory diagnoses among OST patients, which likely indicates underdiagnosing in this patient group [ 23 ]. Spithoff et al showed that patients in OST were less likely to receive diabetes monitoring than matched controls [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation